Evaluation of children and adolescent with cystic fibrosis by pancreatic elastography. Issue 1 (28th February 2022) - Yılmaz, Kamil; Hattapoğlu, Salih; Şen, Velat; Karabel, Müsemma; Kan, Ahmet; Yılmaz, Engin Deniz; Selimoglu Sen, Hadice; Yılmaz, Sureyya
Abstract: Background: Cystic fibrosis (CF) is an autosomal recessively inherited disease. Clinical findings vary by age of the patient, the organ systems involved, and the severity of the CFTR gene mutation. Pancreatic and liver involvement is prominent and exocrine pancreatic insufficiency is observed in the majority of patients. Point shear wave elastography (pSWE) is a non‐invasive method that can quantitatively determine tissue elasticity and stiffness. In this study, the morphological evaluation of the pancreas was performed using the pSWE technique in pediatric patients diagnosed with CF. The effectiveness of this method for the early detection of pancreatic insufficiency was investigated. Methods: Fifty‐five patients with CF (24 girls, 31 boys) and 60 healthy children (29 girls, 31 boys) without any chronic diseases and who were suitable for the pSWE examination were included in the study. Results: The mean value of pSWE was 1.12 ± 0.16 in the healthy group and 0.97 ± 0.16 in the patients with cystic fibrosis. There was a statistically significant difference between the two groups ( P < 0.001). Significant negative correlations were found between pSWE and age (r = −0.319; P = 0.018), height (r = −0.293; P = 0.03), serum glucose (r = −0.346; P = 0.01), HbA1C (r = −0.592; P = 0.02), and duration of the disease (r = −0.806; P < 0.001). Conclusions: Investigating pancreatic elasticity and detecting pancreatic insufficiency using pSWE (a simple, inexpensive, and non‐invasive method) in the early period before overt laboratory and clinical symptoms of EPI appear can contribute positively to long‐term results in young patients with CF.